Comparison of pressure-controlled volume-guaranteed ventilation and volume-controlled ventilation in obese patients during gynecologic laparoscopic surgery in the Trendelenburg position - Toker,Melike Korkmaz (2019)
Abstract Background and objectives: The aim of this study was to investigate the efficacy of the pressure-controlled, volume-guaranteed (PCV-VG) and volume-controlled ventilation (VCV) modes for maintaining adequate airway pressures, lung compliance and oxygenation in obese patients undergoing laparoscopic hysterectomy in the Trendelenburg position. Methods: Patients (104) who underwent laparoscopic gynecologic surgery with a body mass index between 30 and 40 kg.m-2 were randomized to receive either VCV or PCV-VG ventilation. The tidal volume was set at 8 mL.kg-1, with an inspired oxygen concentration of 0.4 with a Positive End-Expiratory Pressure (PEEP) of 5 mmHg. The peak inspiratory pressure, mean inspiratory pressure, plateau pressure, driving pressure, dynamic compliance, respiratory rate, exhaled tidal volume, etCO2, arterial blood gas analysis, heart rate and mean arterial pressure at 5 minutes after induction of anesthesia in the and at 5, 30 and 60 minutes, respectively, after pneumoperitoneum in the Trendelenburg position were recorded. Results: The PCV-VG group had significantly decreased peak inspiratory pressure, mean inspiratory pressur, plateau pressure, driving pressure and increased dynamic compliance compared to the VCV group. Mean PaO2 levels were significantly higher in the PCV-VG group than in the VCV group at every time point after pneumoperitoneum in the Trendelenburg position. Conclusions: The PCV-VG mode of ventilation limited the peak inspiratory pressure, decreased the driving pressure and increased the dynamic compliance compared to VCV in obese patients undergoing laparoscopic hysterectomy. PCV-VG may be a preferable modality to prevent barotrauma during laparoscopic surgeries in obese patients.